2022
DOI: 10.1021/acs.jctc.2c00568
|View full text |Cite
|
Sign up to set email alerts
|

Probing Methyl Group Dynamics in Proteins by NMR Cross-Correlated Dipolar Relaxation and Molecular Dynamics Simulations

Abstract: Nuclear magnetic resonance (NMR) spin relaxation is the most informative approach to experimentally probe the internal dynamics of proteins on the picosecond to nanosecond time scale. At the same time, molecular dynamics (MD) simulations of biological macromolecules are steadily improving through better physical models, enhanced sampling methods, and increased computational power, and they provide exquisite information about flexibility and its role in protein stability and molecular interactions. Many example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…CHARMM36m (C36m) was combined with TIP4P/2005 water as we have previously shown this combination to yield good results for IDPs, including the homologous N TAIL protein from Sendai virus . Holonomic constraints were applied on the hydrogen-heavy atom bond terms to remove fast modes of oscillation, and a cutoff of 1.2 nm was used for the Lennard-Jones and electrostatic interactions (this has been shown to exert negligible impact on calculated relaxation rates). Particle-mesh Ewald summation with a grid spacing of 0.16 nm was used to calculate long-range electrostatic interactions .…”
Section: Methodsmentioning
confidence: 99%
“…CHARMM36m (C36m) was combined with TIP4P/2005 water as we have previously shown this combination to yield good results for IDPs, including the homologous N TAIL protein from Sendai virus . Holonomic constraints were applied on the hydrogen-heavy atom bond terms to remove fast modes of oscillation, and a cutoff of 1.2 nm was used for the Lennard-Jones and electrostatic interactions (this has been shown to exert negligible impact on calculated relaxation rates). Particle-mesh Ewald summation with a grid spacing of 0.16 nm was used to calculate long-range electrostatic interactions .…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, we find the biggest improvement for VAL70. It was previously shown that VAL70 undergoes slow motions that are linked to rotameric jumps, 63,64 and previous work showed imperfect agreement between simulations and experiments for this residue for some, 29 but not all, 19 relaxation measurements. We find that the χ 1 rotamer distribution of VAL70 changes upon reweighting and the increase of the trans population with the coupled decrease of the gauche-rotamer population is also in better agreement with experimentally obtained rotamer populations by Chou et al 63 (Figure 3K).…”
Section: Reweighting MD Trajectoriesmentioning
confidence: 91%
“…The integration of NMR and MD has proven to be particularly useful both to interpret experiments but also for the validation and parametrization of force fields. The underlying mechanisms of NMR spin relaxation experiments are largely understood, and thus relatively good models exist to calculate relaxation rates from MD simulations for both the backbone amides and side chains. ,, In the case of side chain relaxation, it has, however, previously been shown that commonly used force fields did not fully capture the relevant motions or time scales. , In particular, it was demonstrated that calculated and experimental deuterium relaxation rates for the fast dynamics of methyl-bearing amino acids did not match within experimental error. Hoffman and co-workers suggested that this was in part due to too high methyl rotation barriers and reparametrized the corresponding force constants of methyl-bearing amino acids using CCSD­(T) coupled cluster quantum chemical calculations of isolated dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of NMR and MD has proven to be particularly useful both to interpret experiments [16][17][18][19][20] but also for the validation and parameterisation of force fields. [21][22][23][24][25] The underlying mechanisms of NMR spin relaxation experiments are largely understood 13 and thus relatively good models exist to calculate relaxation rates from MD simulations for both the backbone amides and side chains.…”
Section: Introductionmentioning
confidence: 99%